2011
DOI: 10.2215/cjn.08350910
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Markers and Risk of Cerebrovascular Events in Patients Initiating Dialysis

Abstract: SummaryBackground and objectives Stroke remains a leading cause of morbidity and mortality for patients on dialysis; however, its risk factors in this population and measures to prevent it are not well understood.Design, setting, participants, & measurements We investigated whether inflammation was associated with cerebrovascular events in a national US cohort of 1041 incident dialysis patients enrolled from October 1995 to June 1998 and followed until January 31, 2004. Incident cerebrovascular events were def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
4
1
Order By: Relevance
“…It has been reported that HD patients show a higher rate of silent cerebral infarctions, which is reflected by elevated CRP [18]. On the other hand, another report found no association between CRP level and risk of cerebrovascular events in HD patients [19].We observed that predialysis serum potassium concentration was lower in hemorrhagic stroke patients. A study in rats showed that a high potassium diet allowed cerebral arteries to withstand high blood pressure and reduced damage to the artery wall, thereby preventing brain hemorrhage and infarct and lowering mortality rate.…”
Section: Discussioncontrasting
confidence: 44%
“…It has been reported that HD patients show a higher rate of silent cerebral infarctions, which is reflected by elevated CRP [18]. On the other hand, another report found no association between CRP level and risk of cerebrovascular events in HD patients [19].We observed that predialysis serum potassium concentration was lower in hemorrhagic stroke patients. A study in rats showed that a high potassium diet allowed cerebral arteries to withstand high blood pressure and reduced damage to the artery wall, thereby preventing brain hemorrhage and infarct and lowering mortality rate.…”
Section: Discussioncontrasting
confidence: 44%
“…There are several reasons why these analyses may have underestimated the true magnitude of any adverse effect of blood pressure in dialysis patients. First, measurement of blood pressure once a patient's kidney disease has progressed to require dialysis may not represent past exposure because: (a) blood pressure is modified by both dialysis and medication, and is generally treated to a guideline target (80% of US dialysis patients are prescribed at least one antihypertensive drug ); and (b) long‐standing hypertension (and other cardiovascular diseases) can lead to lower blood pressure by reducing cardiac contractility . The majority of incident dialysis patients have evidence of structural heart disease which worsens with increasing dialysis vintage .…”
Section: Stroke Risk Factorsmentioning
confidence: 99%
“…It has been reported that HD patients show a higher rate of silent cerebral infarctions, which is reflected by elevated CRP [18]. On the other hand, another report found no association between CRP level and risk of cerebrovascular events in HD patients [19].…”
Section: Discussionmentioning
confidence: 99%